Pengaruh Penerapan Green Accounting dan Kinerja Lingkungan Terhadap Kinerja Keuangan PT. Komering Jaya Perdana - Salma, Zahara; Nafis, Ahmad Fauzan; Putri, Poviola Chairani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The application of green accounting and environmental performance to the financial performance of companies has become a very relevant research topic. This study aims to examine the influence of the implementation of green accounting and environmental performance on the company's financial performance. The results of the study show that the application of green accounting and environmental performance has no effect on the financial performance of a company. However, several previous studies have found that environmental accounting distance or green accounting has an important effect on financial performance. The application of green accounting can improve the company's environmental performance which ends in improving financial performance and environmental benefits that can be managed and preserved properly in accordance with government regulations.